2014
DOI: 10.1007/s10661-014-3728-3
|View full text |Cite
|
Sign up to set email alerts
|

A pragmatic approach to study the groundwater quality suitability for domestic and agricultural usage, Saq aquifer, northwest of Saudi Arabia

Abstract: The present study deals with detailed hydrochemical assessment of groundwater within the Saq aquifer. The Saq aquifer which extends through the NW part of Saudi Arabia is one of the major sources of groundwater supply. Groundwater samples were collected from about 295 groundwater wells and analyzed for various physico-chemical parameters such as electrical conductivity (EC), pH, temperature, total dissolved solids (TDS), Na(+), K(+), Ca(2+), Mg(2+), CO3 (-), HCO3 (-), Cl(-), SO4 (2-), and NO3 (-). Groundwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(27 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…4) showed that the majority of the samples are in the rock-water interaction dominance field, suggesting that chemical weathering of rocks forming minerals and evaporation are the dominant processes controlling the major ion composition of the water through the dissolution of the rock-forming minerals. Similar results were found by other studies conducted in arid regions (e.g., Magesh et al 2013;Al-Harbi et al 2014;Huang et al 2014;Nazzal et al 2014;Aly 2014;Saber et al 2014). …”
Section: Hydrochemical Quality Of Groundwater Resourcessupporting
confidence: 91%
See 1 more Smart Citation
“…4) showed that the majority of the samples are in the rock-water interaction dominance field, suggesting that chemical weathering of rocks forming minerals and evaporation are the dominant processes controlling the major ion composition of the water through the dissolution of the rock-forming minerals. Similar results were found by other studies conducted in arid regions (e.g., Magesh et al 2013;Al-Harbi et al 2014;Huang et al 2014;Nazzal et al 2014;Aly 2014;Saber et al 2014). …”
Section: Hydrochemical Quality Of Groundwater Resourcessupporting
confidence: 91%
“…A number of techniques and methods have been developed to interpret the hydro-chemical data of groundwater and evaluate its suitability for drinking by interpreting the analyses of water quality and illustrating its characteristics on maps (SadatNoori et al 2014;Magesh et al 2013). Some of these techniques (e.g., Piper 1944;Gibbs 1970;Wilcox 1955;Doneen 1964;Chadha 1999) can present such analyses in graphical form and have been used in many parts of the world including arid and semi-arid regions (Kortatsi et al 2009;Ayuba et al 2013;Aly et al 2014;Nazzal et al 2014;Kraiem et al 2014) to show ionic concentrations in groundwater samples.…”
Section: Introductionmentioning
confidence: 99%
“…These factors can cause severe degradation to the quality and quantity of groundwater resources [1,2]. Studies conducted in different parts of the Saq and overlying aquifers suggested that groundwater resources are quantitavely over-exploited [3,4] and facing quality deterioration through increased human interaction and rock water interaction [5][6][7][8]. For sustainable solutions, groundwater resources need to be protected from over-exploitation and quality deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of excessive amounts of ions in irrigation water affects soil's physical and chemical properties, reduce soil productivity, create crop toxicity and eventually reduce yields (Kraiem et al, 2014;Nag, 2014;Varol & Davraz, 2015). Major water quality problems for irrigation are salinity, sodicity and alkalinity (Simsek & Gunduz, 2007;Sadashivaiah et al, 2008;Nazzal et al, 2014). An appropriate assessment of water for irrigation requires the determination of of physical, chemical and biological parameters that are greatly influenced by geological formations and anthropogenic activities (Sarath Prasanth et al, 2012;Al-Khashman & Jaradat, 2014;Al-Harbi et al, 2014) and directly related to the classifying of water quality (Saber et al, 2014;Aly, 2014;Aly et al, 2014).…”
Section: Introductionmentioning
confidence: 99%